The love note [large type] - Politano, Joanna Davidson, 1982- (Thorndike Press large print Christian romance, 2021)
"Focused on a career in medicine and not on romance, Willa Duvall is thrown slightly off course during the summer of 1865 when she discovers a never-opened love letter in a crack of her old writing desk. Compelled to find the passionate soul who penned it and the person who never received it, she takes a job as a nurse at the seaside estate of Crestwicke Manor.Everyone at Crestwicke has feelings--mostly negative ones--about the man who wrote the letter, but he seems to have disappeared. With plenty of enticing clues but few answers, Willa's search becomes even more complicated when she misplaces the letter and it passes from person to person in the house, each finding a thrilling or disheartening message in its words. Laced with mysteries large and small, this romantic Victorian-era tale of love lost, love deferred, and love found is sure to delight. ("--